Same old song and dance? An analysis of legislative activity in a period of penal reform - Campbell, Michael (Punishment & society, 2020)
After years of tough-on-crime politics and increasingly punitive sentencing in the United States, economic, political, and social shifts in the 21st century have created new opportunities for opponents of the penal status quo. By 2013, a majority of states had enacted some type of reform aimed at reducing prison populations. An emerging body of punishment and society scholarship seeks to understand the possibilities and characteristics of reform efforts by examining enacted state legislation. In this article, we use a unique data set of all proposed and passed bills in three legislative sessions in New Jersey between 2001 and 2013 to provide a nuanced empirical account of change and continuity in penal logics in the period of reform. Even when not enacted, proposed legislation shapes the penal field by introducing new ideas that are later incorporated into rhetoric, policy, or practice. Proposed bills that never become law can also alter the political calculus for reformers or their opponents. Our findings demonstrate that by expanding our universe of data, we gain insight into characteristics of “late mass incarceration” that we might otherwise miss. In particular, while we find evidence of decarceration and bifurcation logics, our analysis also demonstrates that state lawmakers continue to participate in “crime control theater” and reproduce the same punitive penal logics that helped build the carceral state.